Molecular and Supramolecular Structures of Cd(II) Complexes with Hydralazine-Based Ligands; A New Example for Cyclization of Hydrazonophthalazine to Triazolophthalazine - Saied M. Soliman; Raghdaa A. Massoud; Hessa H. Al-Rasheed; Ayman El-Faham (Crystals, 2021)
Molecular and supramolecular structures of two polymeric and one trinuclear Cd(II) complex with hydralazine-type ligands were presented. Self-assembly of E-1-(2-(thiophen-2-ylmethylene)hydrazinyl)phthalazine (HL) and CdCl2 gave the 1D coordination polymer [Cd(H2L)Cl3]n*H2O, 1, in which the Cd(II) ion is hexa-coordinated with one cationic monodentate ligand (H2L+) and five chloride ions, two of them acting as connectors between Cd(II) centers, leading to the formation of a 1D coordination polymer along the a-direction. Using DFT calculations, the cationic ligand (H2L+) could be described as a protonated HL with an extra proton at the hydrazone moiety. Repeating the same reaction by heating under reflux conditions in the presence of 1 mL saturated aqueous KSCN solution, the ligand HL underwent cyclization to the corresponding [1,2,4]triazolo[3,4-a]phthalazine-3(2H)-thione (TPT) followed by the formation of [Cd(TPT)(SCN)2]n*H2O, 2, a 1D coordination polymer. In this complex, the Cd(II) is coordinated with one NS-donor TPT bidentate chelate and two bridged μ(1,3)-thiocyanate ions connecting the Cd(II) centers forming the 1D polymer array along the b-direction. Heating E-2-(1-(2-(phthalazin-1-yl)hydrazono)ethyl)phenol HLOH with CdCl2 under reflux condition gave the trinuclear complex [Cd3(Hydralazine)2(H2O)2Cl6], 3, indicating the hydrolysis of the hydrazonophthalazine ligand HLOH during the course of the reaction. Due to symmetry considerations, there are only two different Cd(II) centers having CdN2Cl3O and CdN2Cl4 coordination environments. Hirshfeld topology analysis was used to analyze the solid-state supramolecular structure of the studied complexes.